Recovery of zinc from wastewater by crystallization of smithsonite and hydrozincite using fluidized-bed homogeneous granulation - Paulino, Leah Hannah S.; De Luna, Mark Daniel G.; Lu, Ming-Chun (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Zinc has many uses in industries such as steel galvanization, production of electrical battery negative plates and fossil fuel combustion. The wastewater from these industries contains zinc in large quantities, and if not treated appropriately before disposal, may contaminate water sources that could harm the environment and human health. In this research, the effects of precipitant pH, carbonate to zinc molar ratio, and influent zinc concentration on the removal of zinc ions from wastewater using homogeneous fluidized bed granulation (FBHC) were studied. From the experiments with varying factors, the highest removal efficiency (99.9%) was obtained at a precipitant pH of 10.6, [CO3/[Zn] of 1.2, and influent zinc concentration of 100 mg/L, whereas the highest granulation efficiency (96.7%) was obtained when the influent zinc concentration was 300 mg/L at the same aforementioned precipitant pH and molar ratio. The final residual zinc concentration in the effluent (0.15 mg/L) is well within the limits set by the EPA and WHO (5.0 mg/L). The effect of the presence of anions that were added to the synthetic zinc wastewater, namely chloride, fluoride and nitrate, was also investigated. It was found that the combination of these ions with the wastewater had little and insignificant effects on removal, giving a final residual zinc concentration of0.44 mg/L. Zinc was recovered in the form of zinc carbonate and hydrozincite granules, with pellet diameters up to 2.0 mm. FBHC proved to be an effective alternative to seeded crystallization since the products were of higher purity and the cost of seeding material purchase was eliminated.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Zinc; Sewage -- Purification; Crystallization